HITTING SKILLS IN KASTI BALL GAME USING MODIFIED BATTING AND BALL AID TOOLS IN GRADE V STUDENTS OF SDN Datengan 2 Kediri - Aulia Keri R; Agus Cahyo; M. Anis Zawawi (JOURNAL SAINS STUDENT RESEARCH, 2025)
If the available facilities and infrastructure are useful and the learning process is focused on the needs of students, especially on the material of the game of rounders, PJOK learning in schools will run well. Some factors that influence it include the behavior of the students themselves, such as fear when hitting or a sense of doubt about self-esteem. The purpose of this study was to determine the effect of replacing bats and balls on the ability of 5th grade students of SD Negeri 2 Datengan to play rounders well. Data collection was carried out through student skills tests which included modifications to bats and balls to determine the increase in students' hitting skills. Data analysis used descriptive statistics such as average, standard deviation, and variance, as well as inferential statistics such as normality, t-test, and measurement of improvement. Based on the results of the study, it can be concluded that when bats and balls were modified for students, their hitting skills in the game of rounders increased by more than 90%.